Accuracy of specific gravity assessment days as a measure of layer egg shell quality (Research, Society and Development, 2021)
Specific gravity analysis (SG) is the main indirect method for measuring the quality of hens' eggshells and is widely used in research and by the productive sector.However, there is not standardization in the number of days that are generally used to carry out this assessment. In addition, the ambiental temperature may change over the SG evaluation days and, if elevated, the egg may lose water and carbon dioxide and alter the density of the internal content, masking the results and interfering with the accuracy of the same. Therefore, the objective of this work was to verify the number of days necessary to evaluate the quality of eggs through SG. A completely randomized design was used, in a 3x7 factorial scheme (three days of SG evaluation, and seven saline solutions). The results obtained were submitted to analysis of variance and, when significant, to the Tukey test at 5%. No significant differences were observed (p> 0.05) for SG in the three days evaluated, but differences were observed (p